2023
DOI: 10.48048/tis.2023.6485
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Mechanical Properties of Topical Films Containing Ganoderma applanatum using the Design of Experiments

Abstract: With the guidance of Design-Expert® software version 11, the mechanical properties of topical films containing Ganoderma applanatum (G. applanatum) extracts were investigated. While ethyl cellulose (EC), G. applanatum extracts, and triethyl citrate (TEC) were independent factors, ultimate tensile strength (UTS), elongation at break, and folding endurance were dependent variables. The best relationships between UTS, elongation at break, and folding endurance could be predicted more accurately using quadratic, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The model's significance was verified by the UTS's ANOVA results, which had adequate precision of 5.9576. The "predicted R-squared" value of 0.9645 and the "adjusted R-squared" value of 0.9589 were both quite close to the actual result [7]. The model's F-value of 4.21 indicated that it was significant, and the probability of a significant "F-value model" owing to noise was 0.01 %.…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…The model's significance was verified by the UTS's ANOVA results, which had adequate precision of 5.9576. The "predicted R-squared" value of 0.9645 and the "adjusted R-squared" value of 0.9589 were both quite close to the actual result [7]. The model's F-value of 4.21 indicated that it was significant, and the probability of a significant "F-value model" owing to noise was 0.01 %.…”
Section: Resultssupporting
confidence: 71%
“…In this instance, the model parameters "silicone rubber×mefenamic acid", "silicone rubber×DBS", "mefenamic acid×DBS", "silicone rubber 2 ", "mefenamic acid 2 " and "DBS 2 " were important (Figures 2 -3). The model's significance was verified by the ANOVA results, which had adequate precision of 9.5849 and 4.2353 for elongation at break and folding endurance, respectively [7]. The ratio was more than 4, indicating that the model could predict results inside the design space without the need for additional tests.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations